2019
DOI: 10.7759/cureus.5373
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Cannabis Use and Risk of Complications in Patients with Chronic Hepatitis C

Abstract: Objectives To evaluate the risk of complication in hospitalized chronic hepatitis C (CHC), patients with cannabis use disorder (CUD). Methods We conducted a retrospective study using the nationwide inpatient sample (NIS), and included 31,623 patients (age 15-54) with a primary international classification of diseases, ninth revision (ICD-9) diagnosis for CHC and grouped by co-diagnosis of CUD (1101, 3.5%). Logistic regression model adjusted for confounders was used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…About one-third of patients with chronic hepatitis and liver diseases have alcohol use problems, including abuse and dependence [12]. CALD leads to decreased synthesis of clotting and inhibitor factors, decreased clearance of activated factors, quantitative and qualitative platelet defects, hyperfibrinolysis, and accelerated intravascular coagulation [13].…”
Section: Discussionmentioning
confidence: 99%
“…About one-third of patients with chronic hepatitis and liver diseases have alcohol use problems, including abuse and dependence [12]. CALD leads to decreased synthesis of clotting and inhibitor factors, decreased clearance of activated factors, quantitative and qualitative platelet defects, hyperfibrinolysis, and accelerated intravascular coagulation [13].…”
Section: Discussionmentioning
confidence: 99%
“…[ 283 ] Some observational studies identified associations between cannabis and accelerated hepatic fibrosis, encephalopathy, and ascites in patients with chronic LD attributable to HCV and fatty liver disease. [ 284–287 ] However, other observational studies, including two meta‐analyses of marijuana use and HCV, did not find a significant association between cannabis and hepatic fibrosis. [ 288–291 ] Trials of medical cannabinoids/marijuana have generally excluded patients with cirrhosis, given their vulnerability to neuropsychiatric symptoms.…”
Section: Abdominal Distension Attributable To Refractory Ascitesmentioning
confidence: 99%
“…About 10% to 20% of patients who are heavy drinkers develop alcohol-related liver diseases [8]. About 36% of patients with chronic hepatitis have alcohol dependence or abuse problems [9]. Hospital admission in alcoholic liver disease has increased by 18.3% [10] from 2012 to 2016.…”
Section: Introductionmentioning
confidence: 99%